The socioeconomics and management of Santiago de Chile's public urban forests (2006)
Santiago, Chile's semi-arid climate and urbanized environment poses a severe limitation for the establishment and maintenance of urban forests. Municipalities, or comunas, are the main stakeholders in the management of Santiago's public urban forests. A tenable hypothesis would be that as the socioeconomic level of a comuna increases, the better the condition of a comuna's urban forest. Unfortunately, there is little comprehensive information on management, public expenditure, and structure of Santiago's public and private urban forests. To examine this hypothesis, Santiago was divided into socioeconomic strata, then using air photo interpretation and stratified field sampling, urban forest structures were quantified by socioeconomic strata. In addition, interview surveys were used to determine municipal urban forest management and expenditures for different public urban forests based on socioeconomic strata. Urban forests in the high socioeconomic strata had fewer public trees, greater tree cover, tree and leaf area density, and leaf area index than lower socioeconomic strata. The percentage of total municipal budget allocated to public urban forest management was consistent among strata, but the total public urban forest budgets were greater in the high socioeconomic strata. Public urban forest structure is related to the socioeconomic strata of Santiago's different comunas.